Surface Metrology for Process Diagnostic of Ultrasonic Vibration Assisted Grinding - Ismail, Mohd Fauzi; Jamian, Rahim; Yahaya, Mohamad Irwan; Isobe, Hiromi (International Journal of Integrated Engineering, 2022)
The application of electroplated diamond in ultrasonic vibration-assisted grinding can be a candidate to replace the manual mirror finishing of the stainless-steel surface and the ability to characterize the tool and work surfaces is important for understanding the tool-work interaction during the grinding process. In this study, an ultrasonic vibration-assisted grinding on stainless steel surface using the electroplated diamond tool is performed for the tool-work surface interaction diagnostic. The experiment used constant machining parameters, leaving the electroplated diamond tool as the only input variable. The experiment produces nine tool-work pairs for the analysis. A combination of the reversal method and areal surface metrology is introduced to capture and prepare the topography data for characterization. The analysis results show that the combination of the reversal method and areal surface metrology can be used for the electroplated diamond tool working surface characterization in explaining its effect on the ultrasonic vibration-assisted grinding of stainless-steel surface for a mirror finish.